Influence of mentoring on achievement motivation in leadership role as perceived by extension workers in Iran - Roya, Karami; Ismail, Maimunah; Abdul Wahat, Nor Wahiza; Omar, Zoharah (2011)
Purpose-The purpose of this paper is to examine the influence of mentoring on achievement motivation in leadership role by considering the mediating effect of self-efficiacy. The study focuses on extension workers because leadership is a fundamental task of these human resource professionals. Design/Methodology/Approach-The respondents of this study were 123 extension workers of Jihad-e-Agriculture organizations of Kermanshah and Tehran provinces, Iran. Sample size was determined using Structural Equation Modeling (SEM) procedures. A questionnaire was prepared as the instrument of the study and it was distributed using 'drop-and-pick' procedures to the respondents. Achievement motivation was measured through three dimensions, namely aspiration, mastery and salience. Self-efficacy was assessed using General Self-Efficacy Scale (GSE).Mentoring was measured based on its career function. Findings-The study results show that extensions workers' self-efficacy is significantly increased by mentoring, and self-efficacy is positively related to achievement motivation. The study further supports the partial meadiating effect of self-efficacy on the relationship between mentoring and achievement mootivation of the extension workers. Practical implications-The study has practical implications in mentoring at the workplace. Organizations could see the potential of mentoring as a powerful learning and development strategy which could be used in employee training at workplace. Originality/Value-This article offers a valuable insight into the role of mentoring on achievement motivation in leadership role by considering the mediating effect of self-efficacy based on the context of extension system in Iran.